(untitled) (Papeles, 2019)
It’s not very often that exam preparation manuals are reviewed in journals. However, considering the global scope and impact of Cambridge testing on knowledge, seemingly feedback from educators and content practitioners would serve in terms of updating manuals and their pedagogical paradigms.